2023
DOI: 10.1007/s12672-023-00736-w
|View full text |Cite
|
Sign up to set email alerts
|

Rapid identification of endometrial hyperplasia and endometrial endometrioid cancer in young women

Dan Kuai,
Qingtao Tang,
Wenyan Tian
et al.

Abstract: Purpose We investigated endometrial hyperplasia (EH) and endometrial endometrioid cancer (EEC) and developed a nomogram model to predict the EH/EEC risk and improve patients’ clinical prognosis. Methods Data were collected from young females (age: ≤ 40 years) who complained of abnormal uterine bleeding (AUB) or abnormal ultrasound endometrial echoes. The patients were randomly divided into training and validation cohorts at a 7:3 ratio. The risk fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The American College of Obstetricians and Gynecologists Committee reported that in AH patients, approximately 25-40% of patients experience EEC simultaneously, and the EEC risk was increased by 14-45 times. 1 Among women, obesity is more strongly associated with the development of endometrial cancer than any other cancer type. In fact, approximately 57% of endometrial cancers in the United States are thought to be attributable to being overweight and obese.…”
Section: Introductionmentioning
confidence: 99%
“…The American College of Obstetricians and Gynecologists Committee reported that in AH patients, approximately 25-40% of patients experience EEC simultaneously, and the EEC risk was increased by 14-45 times. 1 Among women, obesity is more strongly associated with the development of endometrial cancer than any other cancer type. In fact, approximately 57% of endometrial cancers in the United States are thought to be attributable to being overweight and obese.…”
Section: Introductionmentioning
confidence: 99%